The last mile(s) in modern input distribution: Pricing, profitability, and adoption - Minten, Bart; Koru, Bethlehem; Stifel, David (Wiley, 2013)
Increasing adoption of modern inputs remains one of the best hopes for greater agricultural production in developing countries. Based on unique data from northwestern Ethiopia, this study examines the “last mile(s)”—from the input distribution center to the farmer—in the chemical fertilizer and improved seed distribution system. We find that increasing transaction and transportation costs over a 35 km distance, along a route mainly accessible to only foot traffic, lead to a 50% increase of the price of chemical fertilizer and to a 75% reduction in its use. Farmers who live about 10 km from the distribution center face per unit transaction and transportation costs as high as the costs needed to bring the fertilizer from the international port to the input distribution center (about 1,000 km). Tackling the “last mile(s)” costs should thus be a priority to improve modern input adoption and use in these settings.